Cyberbullying on Students’ Blog: Exploring Bully in Digital Era - Budianto Hamuddin; Syahdan Syahdan; Kurniawan Kurniawan (ELT-Lectura, 2018)
cyberbullying phenomenon among EFL students interactive communication somehow an exciting topic to discuss. Seeing foreign language speakers interact and communicate with each other on the internet, this is an interesting linguistic study for review. This present library study tries to explore ten high recognized papers from contemporary studies regarding cyberbullying among students’ interactive communication. From these ten studies, this ongoing study constructs its perspective in seeing the cyberbullying context. This study uses a library study in qualitative approach and explores ten contemporary research about cyberbullying and came out with a result of present perspective and currently proposed terminology of cyberbullying among EFL bloggers.